COMPARATIVE PROFESSIONAL ACCOUNTANCY–NETHERLANDS AND BELGIUM. - Murphy, Mary E. (The Accounting Review, 1960)
Abstract The first treatise on double-entry bookkeeping published in Dutch appeared in 1543. With the early foundation of bookkeeping in the Netherlands, it is surprising that the profession developed so slowly and so late. It was not until 1880 that the first public accountant's office was established there, but by 1905 there were four societies of accountants in existence. The oldest professional body is Het Nederlandsch Instituut dan Accountants, founded in 1895, with a membership originally divided into first and second class. The four professional bodies were amalgamated in 1934 under the title, Het Nederlandsch Instituut van Accountants, its headquarters is at Herengracht 491, Amsterdam. The Netherlands Institute was established on English lines, its founders having been especially influenced by The Institute of Chartered Accountants in England and Wales. In the early years, the accountant was regarded merely as an expert and confidential adviser to his client. In the course of time, attention was directed to the accountant's third-party relations.